2019
DOI: 10.2174/1567205016666181212162424
|View full text |Cite
|
Sign up to set email alerts
|

The Temporal Relationship between Pain Intensity and Pain Interference and Incident Dementia

Abstract: Background: Chronic pain is common among older adults and is associated with cognitive dysfunction based on cross-sectional studies. However, the longitudinal association between chronic pain and incident dementia in community-based samples is unknown. Objective: We aimed to evaluate the association of pain intensity and pain interference with incident dementia in a community-based sample of older adults. Methods: Participants were 1,114 individuals 70 years of age or older from Einstein Aging Study (EAS),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 41 publications
4
49
2
Order By: Relevance
“…T, t value; P, P value; X, X-coordinate; Y, Y-coordinate; Z, Z-coordinate. Pain-VAS, subjective level of pain measured by VAS These two conditions (pain and cognitive dysfunction) are demonstrably interrelated [11][12][13][14]43], and pain has been identified as a risk factor for dementia [17]. However, the neural mechanisms underlying their interaction remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…T, t value; P, P value; X, X-coordinate; Y, Y-coordinate; Z, Z-coordinate. Pain-VAS, subjective level of pain measured by VAS These two conditions (pain and cognitive dysfunction) are demonstrably interrelated [11][12][13][14]43], and pain has been identified as a risk factor for dementia [17]. However, the neural mechanisms underlying their interaction remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The filtered data were used directly for source-level analyses. To identify the specific locations of the brain regions responsible for producing the resting-state-induced components, source inversion procedures were applied separately to the oscillation components of delta (0-3 Hz), theta (4-7 Hz), alpha (8-12 Hz), beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), and gamma (low gamma, 26-40 Hz; high gamma, 41-80 Hz). We used a maximal smoothness algorithm with a spatially coherent source model (i.e., COH algorithms implemented in SPM-12) [35], which is comparable to standardised low-resolution brain electromagnetic tomography (sLORETA) [36].…”
Section: Meg Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the Einstein Aging Study, Ezzati et al (2019) assessed the connection of pain intensity, as well as pain interference with incident dementia in 1,114 participants who were 70 years of age or older and 10% of the participants, developed dementia over 4.4 years. In this study, it has been observed that higher levels of pain interference are directly connected with a higher possibility of developing dementia (Ezzati et al, 2019). In a study by Ikram et al (2019) also advocated that pain interference was considerably linked with AD and related dementia (ADRD).…”
Section: Pain Cognitive Impairment and Admentioning
confidence: 99%
“…BPSD include depressive symptoms that can be linked to unrelieved pain. Incidentally, persistent and chronic pain per se represents risk factors for cognitive decline and dementia (see [20][21][22]). Previous work from our group has demonstrated accuracy of treatment of inflammatory pain, but limited access to the treatment of chronic and neuropathic pain in demented patients in Calabria in the period 2014-2016 [23,24].…”
Section: Introductionmentioning
confidence: 99%